Effects of Coil Orientation on Motor Evoked Potentials From Orbicularis Oris - Adank, Patti; Kennedy-Higgins, Dan; Maegherman, Gwijde; Hannah, Ricci; Nuttall, Helen E. (Frontiers in Neuroscience, 2018)
This study aimed to characterise effects of coil orientation on the size of Motor Evoked Potentials (MEPs) from both sides of Orbicularis Oris (OO) and both First Dorsal Interosseous (FDI) muscles, following stimulation to left lip and left hand Primary Motor Cortex. Using a 70mm figure-of-eight coil, we collected MEPs from eight different orientations while recording from contralateral and ipsilateral OO and FDI using a monophasic pulse delivered at 120% active motor threshold. MEPs from OO were evoked consistently for six orientations for contralateral and ipsilateral sites. Contralateral orientations 0°, 45°, 90°, and 315° were found to best elicit OO MEPs with a likely cortical origin. The largest FDI MEPs were recorded for contralateral 45°, invoking a posterior–anterior (PA) current flow. Orientations traditionally used for FDI were also found to be suitable for eliciting OO MEPs. Individuals vary more in their optimal orientation for OO than for FDI. It is recommended that researchers iteratively probe several orientations when eliciting MEPs from OO. Several orientations likely induced direct activation of facial muscles.